(untitled) (Scientia Agricola, 1994)
The mobility of the main cátions and the mineralógical evolution are studied for a weathering sequence of a diabase, from unaltered rock to the rock-derived soil. The diabase is located in conditions of subhumid and subtropical weather, having good drainage, located in Capivari (SP), Brazil. The mineralogy of diabase, essentialy constitued of plagioclases and pyroxenes, developed to a simple mineralogy, in which the clay fraction of the soil consists only of kaolinite, associated to non determined iron oxides. Vermiculite occurs in the intermediary stages, as the only 2:1 clay mineral. The leaching of soluble cátions occurs rapidly in the first stages of the process, followed by silica, also with rapid removal, however due to its high concentration in the original rock, it remains longer time in the system, in the structure of kaolinite and also as quartz in small quantity. Aluminium and iron are immobilized in the system, aluminium in the structure of kaolinite and iron as oxide.